Chemopreventive opportunities to control basal cell carcinoma: Current perspectives. Issue 9 (5th June 2015) - Tilley, Cynthia; Deep, Gagan; Agarwal, Rajesh
<x xml:space="preserve">Abstract</x> Basal cell carcinoma (BCC) is a major health problem with approximately 2.8 million new cases diagnosed each year in the United States. BCC incidences have continued to rise due to lack of effective chemopreventive options. One of the key molecular characteristics of BCC is the sustained activation of hedgehog signaling through inactivating mutations in the tumor suppressor gene patch (Ptch) or activating mutations in Smoothened. In the past, several studies have addressed targeting the activated hedgehog pathway for the treatment and prevention of BCC, although with toxic effects. Other studies have attempted BCC chemoprevention through targeting the promotional phase of the disease especially the inflammatory component. The compounds that have been utilized in pre‐clinical and/or clinical studies include green and black tea, difluoromethylornithine, thymidine dinucleotide, retinoids, non‐steroidal anti‐inflammatory drugs, vitamin D3, and silibinin. In this review, we have discussed genetic and epigenetic modifications that occur during BCC development as well as the current state of BCC pre‐clinical and clinical chemoprevention studies. © 2015 Wiley Periodicals, Inc.